Microfinance Institutions as a Vehicle for Poverty Eradication in Developing Countries: Evidence from the East African Community Member States - Joseph Dushime; Immaculate Nakalembe; Yar Makuei; Albert Kwitonda; Samuel Hakizimana; Stephen Muathe (European Scientific Journal, ESJ, 2022)
This paper focuses on examining the link that exists between microfinance institutions (MFIs) and poverty eradication efforts in developing countries, specifically focusing on the East African member states of Burundi, Democratic Republic of Congo (DRC), Kenya, Rwanda, South Sudan, Tanzania, and Uganda. The study was driven by the varying interpretations, debates, and opposing opinions in literature on the effects of MFIs on poverty eradication in developing economies, particularly in the East African Community (EAC). The study used a depth literature search using secondary data on the role of MFIs in poverty eradication in the EAC context. The results pointed out that despite the challenges such as high transaction rates, limited funding and others, microfinance credit has played a significant role in poverty eradication among poor/low-income families in the EAC Member States. Therefore, the study recommends that governments of the EAC Member States should increase government support, and conducive working environments should be provided to ensure microfinance institutions reach as many less privileged individuals as possible so as to raise their economic status.